The Anthropocene Paradigm in Islamic Education in Indonesia: The Transformation of Thought and Practice in Responding to the Ecological Crisis - Hidayatulloh, Taufik; Saenong, Farid F; Saumantri, Theguh; Hajam, Hajam (LPPM IAIN Kudus, 2026)
Global ecological crises and climate change have evolved into multidimensional problems that not only threaten environmental sustainability but also generate social, economic, and humanitarian crises. In this context, the Anthropocene paradigm emerges as a conceptual framework that explains how human activities have become the dominant factor shaping changes in the Earth system. This study aims to analyze how the Anthropocene paradigm can reconstruct Islamic education through epistemic, curricular, pedagogical, and institutional transformations in responding to the global ecological crisis. This study employed a qualitative approach based on library research using a conceptual paper model. Data were obtained through the examination of various relevant academic literatures and analyzed using content analysis and critical-hermeneutic interpretation techniques. The findings indicate that Islamic education possesses a strong theological foundation through the concepts of tawḥīd (monotheism), khilāfah (stewardship), mīzān (balance), and Maqāṣid al-Sharī‘ah (objectives of Islamic law) in fostering ecological awareness and sustainability responsibility. However, the integration of environmental issues within Islamic education in Indonesia remains predominantly normative and moralistic and has not yet developed into “ecological systems thinking” and “sustainability literacy”. This study emphasizes that the transformation of Islamic education in the Anthropocene era requires the reconstruction of an integrative, ecological, and transformative educational paradigm capable of developing a Muslim generation with planetary consciousness and socio-ecological responsibility toward the sustainability of the Earth.